Adsorption of Methylene Blue by Graft Copolymer Acrylamide onto Pineapple Peel Cellulose with the Addition of Activated Carbon Microwave-Assisted - Permatasari, Putri; Sutriah, Komar; Khotib, Mohammad (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2023)
Cationic dyes such as methylene blue are among the most widely used dye in the textile and paper industry. The dye waste produced causes environmental pollution and is harmful to human health. Thus, wastewater treatment becomes an important aspect of reducing this problem. Adsorption is a very effective method for treating various wastewaters due to its high selectivity and capacity. This study aims to prepare an adsorbent from graft copolymer acrylamide onto cellulose with the addition of activated carbon microwave-assisted and to test its performance as an adsorbent for methylene blue. The adsorbent synthesis was carried out using a microwave-assisted graft copolymer technique. The graft of acrylamide onto cellulose with the addition of activated carbon was carried out at various times (3, 4, and 5 minutes). Based on the FTIR spectra characterization of the adsorbent, the functional groups are C=O and N-H, and SEM analysis shows that the surface forms an interconnected network. At 3, 4, and 5 minutes of irradiation, grafting ratios were 329.72, 128.00, and 150.12, with grafting efficiency of 99.74, 72.94, and 78.02%. The maximum adsorption capacity of the adsorbent on methylene blue was 14.00, 6.04, and 9.97 mg/g, respectively, following the Langmuir isotherm model and pseudo second order kinetics. The experimental results show that the adsorbent can effectively remove or eliminate methylene blue in an aqueous solution.